Impact of Oncological Therapy and Viscum album L Treatment on Cancer-Related Fatigue and Internal Coherence in Nonmetastasized Breast Cancer Patients. (May 2020) - Oei, Shiao Li; Thronicke, Anja; Kröz, Matthias; von Trott, Philipp; Schad, Friedemann; Matthes, Harald
Introduction: Viscum album L extracts (VA) are frequently used in integrative oncology. Aim of this study was to evaluate the impact of add-on VA applications on various patient-reported outcome measures.Methods: A longitudinal real-world study was conducted, using data from the Network Oncology clinical registry. Primary, nonmetastasized breast cancer patients treated with oncological standard therapy partly combined with VA applications were included. Internal Coherence Cancer-related Fatigue, and EORTC QLQ-C30 questionnaires were assessed at baseline and 6, 12, and 24 months later.Results: A total of 319 patients received standard oncological therapy and 40% of them additionally VA applications. After 6 and 12 months for patients treated with chemotherapy (Ctx) only a significant decline of the thermo-coherence, and worsening of fatigue was observed. For patients receiving VA applications but no Ctx, significant beneficial effects on thermo-coherence, fatigue, and seven EORTC QLQ-C30 scales were observed 24 months later. Adjusted multivariable long-term subgroup ( n = 106) regression analysis revealed that Ctx, immuno-, and endocrine therapies had a worsening of 17, 17, and 6 point changes, respectively, for EORTC QLQ-C30 fatigue ( P = .0004), while VA applications showed an improvement of 12 point change. A similar impact of improvement (add-on VA) and worsening (standard oncological treatment regimens) on EORTC QLQ-C30 insomnia ( P = .009) and physical functioning ( P = .005) were observed.Conclusions: In the present real-world study, add-on VA applications had a supportive effect on cancer-related fatigue, insomnia, physical functioning, and thermo-coherence. Thus, VA applications might be suited to alleviate symptom burden during anticancer therapy in breast cancer patients.